Wetlands construídas de fluxo vertical como pós-tratamento de reator Rahlf utilizando águas residuárias de suinocultura - Ito, João Batista Bezerra (2018)
The objective of this research was to evaluate the performance of Wetlands constructed of Vertical Flow vegetated with Heliconia Pisittacorum (WCHP) and Pontederia Parviflora (WCPP) and Wetlands Constructed of Non-Vegetal Vertical Flow (WCNV), on a pilot scale, in the removal of organic matter and nutrients, such as post-treatment of Horizontal Anaerobic Fixed Bed Reactor (RAHLF), using wastewater from pig farms of the experimental farm of the Federal University of Mato Grosso. The methodology consisted of designing and constructing the RAHLF and the Wetlands system built on a pilot scale that was installed and monitored in the area of the Experimental Center for Hydraulics and Environmental Sanitation (CEHISA), in the Campus of Cuiabá / UFMT. The crude effluents from swine were monitored, the treated effluent from the RAHLF reactor, and also the Wetlands system was built with a Hydraulic Detention Time (TDH) of 5 to 10 days. The parameters analyzed were: temperature, pH, electrical conductivity (CE), dissolved oxygen (OD), total dissolved solids (STD), total suspended solids (TSS), color, turbidity, biochemical oxygen demand (BOD) (Nitrogen, Nitrate and Total Nitrogen), Phosphorus (P), Sulphate, according to the methods established by Standard Methods (APHA, 1998). The results showed that there was removal in the Wetlands vegetated with the endemic macrophyte of the Brazilian wetland, the Pontederia Parviflora, with average efficiencies of 84-91%, for BOD55and COD, and 98-93-84% for Nitrite, Nitrate and NT, and of 93% for phosphorus.